2019
DOI: 10.1101/823773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trem-2 promotes emergence of restorative macrophages and endothelial cells during recovery from hepatic tissue damage

Abstract: Macrophages are pivotal in mounting liver inflammatory and tissue repair reactions upon hepatic injury showing remarkable functional plasticity. Nevertheless, the molecular mechanisms determining macrophage transition from inflammatory to restorative phenotypes in the damaged liver remain unclear. Using mouse models of acute (APAP) or chronic (CCl4) drug-induced hepatotoxic injury we show that the immune receptor Trem-2 controls phenotypic shifts in liver macrophages and impacts endothelial cell differentia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…In line with Perugorria et al [ 89 ], we have recently shown that in acute and chronic mouse models of liver disease, Trem-2 is particularly upregulated in a specific macrophage population, named “transition macrophages” [ 99 ]. Transcriptomic analyses showed that absence of Trem-2 impacts the switching from recruited to transition macrophages, with the latter showing muted transcriptional response to oxidative stress and an inability to shut down the inflammatory profile.…”
Section: Macrophages and Endothelial Cells Crosstalksupporting
confidence: 78%
See 1 more Smart Citation
“…In line with Perugorria et al [ 89 ], we have recently shown that in acute and chronic mouse models of liver disease, Trem-2 is particularly upregulated in a specific macrophage population, named “transition macrophages” [ 99 ]. Transcriptomic analyses showed that absence of Trem-2 impacts the switching from recruited to transition macrophages, with the latter showing muted transcriptional response to oxidative stress and an inability to shut down the inflammatory profile.…”
Section: Macrophages and Endothelial Cells Crosstalksupporting
confidence: 78%
“…Interestingly, an endothelial liver damage endothelial cell (LDECs) population showing a distinct transcriptional profile was identified. The accumulation of LDECs significantly correlated to the degree of liver damage and to impaired replenishment of KC compartment [ 99 ] ( Figure 2 ). These results fit the notion that a crosstalk between macrophages and endothelial cells is part of the liver regeneration process after liver injury.…”
Section: Macrophages and Endothelial Cells Crosstalkmentioning
confidence: 99%
“…Despite microbiota composition homogenization in the co-housed mice, APAP treatment (D3) recapitulated the hepatic tissue repair phenotype that we have previously described 17 . Namely, wild-type showed complete recover from hepatic tissue damage at D3 after injury, while Trem-2 KO mice revealed persistent liver damage, as quantified by liver necrosis scoring (Figure 3C).…”
Section: Resultsmentioning
confidence: 51%
“…Finding that Trem-2 modulated the gut microbiota composition in untreated mice prompted us to determine whether this trait was involved in the impaired tissue repair responses observed in Trem-2 KO mice 17 . We performed co-housing experiments followed by administration of APAP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation